2008
DOI: 10.1063/1.2956678
|View full text |Cite
|
Sign up to set email alerts
|

Ag-induced spin-reorientation transition of ultrathin Fe films on Pt(111)

Abstract: The spin-reorientation transition (SRT) was observed when Ag overlayers deposited on Fe∕Pt(111) by magneto-optical Kerr effect measurements. The easy axis of the magnetization changes completely from the in-plane to out-of-plane direction after the coverage of Ag is 1 ML. The polar Kerr intensity and its coercivity as a function of Ag coverage are investigated during SRT. The easy axis of magnetization can be reversed back to the in-plane direction after the Ag overlayers are removed by sputtering. The chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The investigations of well-controlled transition metals on metallic substrates are an important topic in material science because of their scientific significance as well as technological applications, especially in surface alloying, microelectronics, enhancing catalytic activities, and spintronics. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] For instance, adsorption of oxygen on Ag/Pt(111) surface alloy leads to an attractive interaction between adsorbed oxygen atoms while oxygen adsorption is blocked on Ag sites. 1 By optimizing the Pt surface content or the Pt film thickness, unambiguous demonstrations of bimetallic surfaces reaching activities well in excess of that of Pt(111) have been made.…”
mentioning
confidence: 99%
“…The investigations of well-controlled transition metals on metallic substrates are an important topic in material science because of their scientific significance as well as technological applications, especially in surface alloying, microelectronics, enhancing catalytic activities, and spintronics. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] For instance, adsorption of oxygen on Ag/Pt(111) surface alloy leads to an attractive interaction between adsorbed oxygen atoms while oxygen adsorption is blocked on Ag sites. 1 By optimizing the Pt surface content or the Pt film thickness, unambiguous demonstrations of bimetallic surfaces reaching activities well in excess of that of Pt(111) have been made.…”
mentioning
confidence: 99%
“…After an annealing treatment for a 5 ML Fe/Pt(111) layer to form a surface alloy, the coercive force is greatly enhanced by as much as 1100%, and the resulting magnetic properties are strongly related to the diffusion of Fe atoms into the Pt(111) substrate 14 . A spin reorientation transition was observed for Fe/Pt(111) ultrathin films by introducing a Ag overlayer as thin as 1 ML 15 . In terms of introducing heterogeneous interfaces, the stabilization of crystallographic phases is critical to a viable strategy for the development of new materials with novel characteristics 17 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Multilayered systems of magnetic and non-magnetic metallic layers, which we have studied, are in particular interesting for their technological applications in the area of data storage and processing [9][10][11] . It has recently been shown that capping a ferromagnetic thin film with a noble metal can influence the magnetic properties [12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%